THE NOTION OF LOGOS FROM THE ANCIENT EGYPTIANS, FINALLY WITH PHILO OF ALEXANDRIA (Heritage, 2021)
The topic of the paper is the notion of logos in certain thinkers and certain philosophical directions. Numerous meanings were ascribed to the Logos to the extent that it could be accepted in different epochs. From the moment of the creation of the human race, man has had the need to know how he exists as a being, and the need to know the world available to his senses. His development of thinking about himself is in fact the development of thinking about the logos. We read this statement in Scripture, where logosity or Divine meaning exists as an intelligible (supersensible / invisible) world.
Keywords: God, Logos, man, world, being